2012
DOI: 10.2478/v10216-011-0022-y
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Mathematical Models for the Atmospheric Dispersion of Heavy Gases. Part I. A Classification of Models

Abstract: Abstract:In this two part article in its first part models of heavy gas dispersion in the atmosphere are classified and the distinguished groups of models are characterised. In the second part the procedures for the model quality evaluation are described and the main results of model evaluation projects are summarised. Substances released to the atmosphere which have a density greater than the density of the atmospheric air are called heavy gases or dense gases. The dispersion of heavy gases is different from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Atmospheric dispersion models (ADMs) may be helpful to describe the dispersion of pathogenic bioaerosols. ADMs are mechanistic models describing the transport of gases and particles -including chemical pollutants, radioactive matter, particulate matter, and dust -in the atmosphere in space and time (Holmes and Morawska, 2006;Markiewicz, 2012;Potempski et al, 2008). ADMs are widely used in the risk assessment of hazardous effects of air pollution on humans and the environment (e.g., Schaap et al, 2013).…”
Section: Atmospheric Dispersion Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atmospheric dispersion models (ADMs) may be helpful to describe the dispersion of pathogenic bioaerosols. ADMs are mechanistic models describing the transport of gases and particles -including chemical pollutants, radioactive matter, particulate matter, and dust -in the atmosphere in space and time (Holmes and Morawska, 2006;Markiewicz, 2012;Potempski et al, 2008). ADMs are widely used in the risk assessment of hazardous effects of air pollution on humans and the environment (e.g., Schaap et al, 2013).…”
Section: Atmospheric Dispersion Modelsmentioning
confidence: 99%
“…Historically, ADMs were often based on the Gaussian dispersion equation (see Section 2.4; Markiewicz, 2012, Millner, 2009) to calculate concentrations at local scales (<30 km) in a three-dimensional frame. Nowadays, most ADMs include important atmospheric processes related to fluid dynamics (e.g., turbulence) as well (Nathan et al, 2005;Upper and Hirano, 1991).…”
Section: Atmospheric Dispersion Modelsmentioning
confidence: 99%
“…However, a set of potential candidates should not be limited to this software. There are many other computer tools available (Markiewicz 2012(Markiewicz , 2018, including the EU Community ADAM module (Fabri and Wood 2019). Wiśniewski et al (2018) have also reported the need to develop legal regulations concerning the assessment of major accident risk in Poland.…”
Section: Conclusion and A Discussion Of The Resultsmentioning
confidence: 99%
“…The algorithm for the diffusion of pollutants can be represented by one of the possible methods, such as: the Gaussian model of the dispersion or the model of the dispersion of heavy gases. Referring to the initial data on the estimated situation of the release of steam-air mixture of petroleum products into atmospheric air, simulation was conducted using a dispersive model of heavy gases [12].…”
Section: Setting the Task And Its Solutionmentioning
confidence: 99%